Riesgos de caídas en los ancianos, un evento multifactorial evitable - Duque, Paula Andrea; Garcés Gómez, Yeison Alberto; Hincapié Ramirez, Doris; Henao Trujillo, Olga María (Cultura del cuidado, 2020)
Falls in the elderly represent important alterations in functionality and are given by intrinsic and extrinsic risk factors, which constitute an increase in morbidity and mortality, so a preventive care plan must be carried out.Objective: To describe the risk factors associated with falls of the elderly in a vulnerable community.Materials and Methods: Descriptive, quantitative, cross-sectional study. Population universe formed by N. 81 older adults who attend the community cafeteria in the San Sebastian neighborhood to receive food for lunch, and the sample obtained was n. 41. Simple random sampling with older adults of both sexes. The instrument that was applied was the Tinetti scale and Short Physical Performance Battery test (SPPB).Results: The analysis of the Tinetti scale was observed balance and gait with an average of 24 points, meaning that older adults have little risk of having a fall, in the SPPB an average of 9 points was obtained, so there is minimal probability of suffering a fall.